2019
DOI: 10.1080/12298093.2019.1625175
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Mechanism of Action of Lauryl Betaine Against Skin-Associated FungusMalassezia restricta

Abstract: Betaine derivatives are considered major ingredients of shampoos and are commonly used as antistatic and viscosity-increasing agents. Several studies have also suggested that betaine derivatives can be used as antimicrobial agents. However, the antifungal activity and mechanism of action of betaine derivatives have not yet been fully understood. In this study, we investigated the antifungal activity of six betaine derivatives against Malassezia restricta , which is the most frequently is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…In this article, novel quaternized carbon dots (QCD) were prepared through a simple carboxylamine reaction between lauryl betaine (LB) and amine‐functionalized carbon dots (AFCD) [28]. LB is a natural product commonly found in human diets, extracted from Beta vulgaris [31]. Previous research had shown that LB exhibited antibacterial activity against Escherichia coli , Salmonella typhimurium , and Staphylococcus aureus [32, 33].…”
Section: Discussionmentioning
confidence: 99%
“…In this article, novel quaternized carbon dots (QCD) were prepared through a simple carboxylamine reaction between lauryl betaine (LB) and amine‐functionalized carbon dots (AFCD) [28]. LB is a natural product commonly found in human diets, extracted from Beta vulgaris [31]. Previous research had shown that LB exhibited antibacterial activity against Escherichia coli , Salmonella typhimurium , and Staphylococcus aureus [32, 33].…”
Section: Discussionmentioning
confidence: 99%
“…Betaine is used as a source of carbon and energy source by fungi as reported by [ 57 ]. Furthermore, the antibacterial activity of betaine has been reported [ 58 ] as well as its activity against skin-associated fungus [ 59 ]. In addition, betaine has an important medicinal value in several human diseases, such as obesity, diabetes, cancer, Alzheimer’s and gastrointestinal diseases [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alkyl betaines 2, or alkylamidopropylbetaines 3 are often introduced in shampoos as antistatic and viscosity-increasing agents (Figure 2). Hee Jung et al tested the antifungal activity of alkyl betaines against M. restricta KCTC 27527 [57]. Among the six betaine derivatives, lauryl betaine 2a exhibited high activity with MIC = 1.5-3 mg/mL.…”
Section: Inhibition Of the Cell Wall And Membrane Biosynthesismentioning
confidence: 99%